2019
DOI: 10.3389/fnins.2019.00783
|View full text |Cite
|
Sign up to set email alerts
|

Safety Aspects, Tolerability and Modeling of Retinofugal Alternating Current Stimulation

Abstract: Background While alternating current stimulation (ACS) is gaining relevance as a tool in research and approaching clinical applications, its mechanisms of action remain unclear. A review by Schutter and colleagues argues for a retinal origin of transcranial ACS’ neuromodulatory effects. Interestingly, there is an alternative application form of ACS specifically targeting α-oscillations in the visual cortex via periorbital electrodes (retinofugal alternating current stimulation, rACS). To further c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Furthermore, the proximity of the optimal montages to the eye regions increases the likelihood of visual phosphenes. While the safety and tolerability of any novel approach have to be carefully evaluated, it is to be noted that certain transcranial approaches, given the application, have actually exploited these high-conductivity pathways to intentionally target these sensitive regions ( Haberbosch et al, 2019 ). Fortunately, not only stimulation parameters (current density, charge density, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the proximity of the optimal montages to the eye regions increases the likelihood of visual phosphenes. While the safety and tolerability of any novel approach have to be carefully evaluated, it is to be noted that certain transcranial approaches, given the application, have actually exploited these high-conductivity pathways to intentionally target these sensitive regions ( Haberbosch et al, 2019 ). Fortunately, not only stimulation parameters (current density, charge density, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The nifti (.nii) color masks from the MIDA model were first processed in MATLAB to re-create segmentation masks based on intensity values. These masks were then imported into Simpleware (Synopsys Ltd., CA, United States), and any errors in continuity and anatomical details were manually corrected for Bikson and Datta (2012) , Datta et al (2012) , Haberbosch et al (2019) . Masks with similar electrical conductivities were then merged to a single compartment excluding the regions of interest (OB and OE) in order to perform detailed individual current flow analysis through them.…”
Section: Methodsmentioning
confidence: 99%
“…As the larger sized electrodes with a diameter of 1 cm were assumed in this study, we strongly believe that it would be safe to inject current much smaller than 3 mA in the proposed montage. In addition, a previous study reported that the maximal electric field amplitude that does not cause any tissue damage is 42 V/m 18 . As much smaller electric field is delivered to the retinal tissues in the suggested montage, the use of the suggested montage will not cause any damage to the retinal tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The calculated electric field was scaled such that the 1 mA of current was flowing into the reference electrode. We assumed that all tissue compartments were homogeneous, and their electrical conductivity values were set according to a previous study 18 . This process was repeated until the electric field distributions for each of the active electrodes were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation